Hosing Down Senior Claims with a Quicker and Dirtier Chapter 11 - Charles W. Mooney Jr. (Washington University Law Quarterly, 1994)
Professors LoPucki and Whitford have written an interesting paper. I shall address some specific points raised in their paper.
Keywords: Bankruptcy reorganization; Debtor and creditor; United States; Investments; Corporate governance